2018
DOI: 10.1063/1.5053884
|View full text |Cite
|
Sign up to set email alerts
|

The direct bandgap of gray α-tin investigated by infrared ellipsometry

Abstract: Using Fourier-transform infrared ellipsometry, the authors provide spectroscopic evidence about the valence band (VB) structure of diamond-like α-tin. The mid-infrared dielectric function of α-tin grown pseudomorphically on InSb or CdTe by molecular beam epitaxy shows a strong E¯0 peak near 0.41 eV. This peak is assigned to allowed intravalence band transitions from the Γ7− (electron-like) VB to the Γ8+v heavy hole VB and/or interband transitions from Γ7− to the Γ8+c light “hole” conduction band. The strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Samples with a significant amount of α-Sn (annealed at 350°C and 375°C) show an additional absorption edge at ∼1750 nm wavelength compared to those with no or little α-Sn, and the absorption further increases with the decrease of wavelength up to 1250 nm. This additional optical absorption feature at ∼0.7-1 eV caused by α-Sn is consistent with a recent work 48 , and it can be attributed to a transition corresponding to the spin-orbit splitting energy of ∆ 0 = Γ 8v − Γ 7v ≈ 0.7eV 1,48 . Moreover, it has been recently demonstrated that pulsed laser can be used to change the quantum states of 3D TDS 39 , so the measured absorption spectrum of α-SnGe suggests that commonly used lasers for telecommunications at 1310-1550 nm may be used for quantum state switching with potential for integration with silicon integrated photonics.…”
Section: Resultssupporting
confidence: 91%
“…Samples with a significant amount of α-Sn (annealed at 350°C and 375°C) show an additional absorption edge at ∼1750 nm wavelength compared to those with no or little α-Sn, and the absorption further increases with the decrease of wavelength up to 1250 nm. This additional optical absorption feature at ∼0.7-1 eV caused by α-Sn is consistent with a recent work 48 , and it can be attributed to a transition corresponding to the spin-orbit splitting energy of ∆ 0 = Γ 8v − Γ 7v ≈ 0.7eV 1,48 . Moreover, it has been recently demonstrated that pulsed laser can be used to change the quantum states of 3D TDS 39 , so the measured absorption spectrum of α-SnGe suggests that commonly used lasers for telecommunications at 1310-1550 nm may be used for quantum state switching with potential for integration with silicon integrated photonics.…”
Section: Resultssupporting
confidence: 91%
“…19), but the discrepancy should be interpreted with caution because the E0 transition in α-Sn has a unique line shape that is not fully understood. 29 The difference between the LC&L prediction and the best fit in Fig. 6(b) has an important practical consequence: LC&L predict a vanishing band gap for y = 0.35, which implies that the 8-12 μm window could be easily covered with Ge-rich Ge1-ySny alloys.…”
mentioning
confidence: 96%
“…For comparison, the electronic structure obtained with the semilocal ONV and GTH PP are given. α-Sn was characterized as zero-bandgap semiconductor, while other earlier experiments reported for α-Sn a bandgap of 0.08 eV . Besides this difference, it is clear that an accurate PP should produce a similar value (a zero or at least a very small bandgap) with a reasonable electronic broadening.…”
Section: Resultsmentioning
confidence: 80%